Primary school in Germany in national and international comparison - Renner, Günter; Grassmé, Isabelle; Reichenbacher, Julia (Docere, 2019)
The article gives a brief overview of the current structure of the German education system and the various shapes it takes, its (school) forms and qualifications. Subsequently, primary school design in Germany will be presented in more detail. This will be followed by an overview of Germany’s performance in various national and international school performance comparisons, focussing on primary schools. A brief outlook shall describe further development
Keywords: primary education; Germany